DIYAT SARIREDJO: PANDANGAN DAN KONSEP PEMIKIRANNYA - Aris Setiawan (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2012)
Diyat Sariredjo is a highly skilled maestro of East Javanese karawitan. His name is often mentioned in relation to thedevelopment of karawitan in East Java at the time when he was a composer, arranger, and head of the karawitan group atRadio Republik Indonesia in Surabaya. Because of the regulation for a routine broadcast of East Javanese karawitan,Diyatâ€™smusical patterns on the kendang and rebabwere usedwidely as a reference by karawitan artists throughout EastJava and in particular in Surabaya.Diyat not only performed East Javanese style gending but also initiated a number ofmonumentalworks of karawitan.Dayat Sariredjomay be said to be the onlymaestro ofEast Javanese karawitanwho is notonly a highly skilled performer but also has the ability to formulate concepts and theories of East Javanese style karawitan.This was supported further by his position as a teacher at Sekolah Menengah Karawitan Indonesia and SekolahTinggiKesenianWilwatikta Surabaya during the 1980s.He transmittedmany thoughts and ideas both to his studentsand colleagues. One of the concepts that Diyat Sariredjomanaged to develop was an analysis of pathet and the sirikantones in compositions of East Javanese karawitan.Diyatâ€™s version of pathet is unique since it is basedmore on the strongseleh of themainmelody (balungan) in a gending (referred to as the tonic). In addition, in order to reinforce the sense ofpathet, every gending has certain â€œprohibitedâ€ noteswhich should be avoided (sirikan). ToDiyat, these notes should beavoided in order that the colour of a particular pathetmay emergemore strongly.On the contrary, if a gending contains toomany of these prohibited notes, the colour or sense of the pathet in a gendingmay become obscure or biased.Keywords:Maestro, concept of thoughts, pathet, prohibited notes.